Development and field test of a high-temperature heat pump used in crude oil heating. (June 2017) - He, Yongning; Cao, Feng; Jin, Lei; Yang, Dongfang; Wang, Xiaolin; Xing, Ziwen
In this paper, a high-temperature heat pump (HTHP) is developed and manufactured to replace the traditional oil-fired boiler heater for crude oil heating. It extracts thermal energy from waste hot water separated from the crude oil to provide high-temperature hot water to heat the crude oil. A prototype of the HTHP system is installed in the Jinzhou oil treatment station in Liaoning, China and the field test is conducted for about 6000 h. A typical 144 h of field testing data is analyzed to evaluate the performance of the designed HTHP system. It is observed that the temperature of hot water provided by the HTHP unit varies from 86 ℃ to 95 ℃ throughout the whole operating period and is sufficient for the crude oil heating (80–90 ℃). The heating capacity and power consumption of the HTHP system varies from 1350 to 1785 kW, and 171 to 197 kW, respectively. The overall system coefficient of performance ranges from 3.5 to 4.4 with an average value of 3.8. Based on the experimental results, a primary energy ratio is introduced to evaluate and compare the economics of the studied HTHP system and oil-fired boiler heater. The comparison shows that the energy consumed by the HTHP unit is only 57% of that consumed by the oil-fired boiler heater. If all traditional oil-fired boiler heaters are replaced by the HTHPs in the Jinzhou oil treatment station, the total yearly energy saving is around 1.12 × 10 4 tons of equivalent coal which equates to 1.76 × 10 4 tons of CO2 emissions.